2021
DOI: 10.1371/journal.pone.0258509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the TEAM Wheels eHealth manual wheelchair training program: Study protocol for a randomized controlled trial

Abstract: Background Variable, and typically inadequate, delivery of skills training following manual wheelchair (MWC) provision has a detrimental impact on user mobility and participation. Traditional in-person delivery of training by rehabilitation therapists has diminished due to cost, travel time, and most recently social distancing restrictions due to COVID-19. Effective alternative training approaches include eHealth home training applications and interactive peer-led training using experienced and proficient MWC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…WheelCon was also used by Giesbrecht and Miller (2017) in their 2017 study of 18 MWUs and their "confidence to operate the device safely and effectively." In Giesbrecht et al (2021) demonstrated their confidence in WheelCon when they designed their study protocol to measure the confidence of MWUs in their training program. Furthermore, a 2019 study by Sol et al (2019) of 62 MWU indicated the WheelCon's validity in measuring CM during their efforts to adapt it to the Dutch population.…”
Section: Self-surveymentioning
confidence: 99%
“…WheelCon was also used by Giesbrecht and Miller (2017) in their 2017 study of 18 MWUs and their "confidence to operate the device safely and effectively." In Giesbrecht et al (2021) demonstrated their confidence in WheelCon when they designed their study protocol to measure the confidence of MWUs in their training program. Furthermore, a 2019 study by Sol et al (2019) of 62 MWU indicated the WheelCon's validity in measuring CM during their efforts to adapt it to the Dutch population.…”
Section: Self-surveymentioning
confidence: 99%
“…Peer-led training, wherein experienced wheelchair users are trained to teach others wheelchair skills through sharing of experiential knowledge, represents one possible solution to expand the delivery of wheelchair skills training into the community [31,32]. Although peer-led training with minimal support of an healthcare professional was effective for improving wheelchair skills and participation in adults [33][34][35], only two case studies have documented the influence of peers on wheelchair skills training in pediatrics.…”
Section: Introductionmentioning
confidence: 99%